2013
DOI: 10.7205/milmed-d-12-00302
|View full text |Cite
|
Sign up to set email alerts
|

Service Utilization Following Participation in Cognitive Processing Therapy or Prolonged Exposure Therapy for Post-Traumatic Stress Disorder

Abstract: This study evaluated the impact of a course of prolonged exposure or cognitive processing therapy on mental health and medical service utilization and health care service costs provided by the Department of Veterans Affairs (VA). Data on VA health service utilization and health care costs were obtained from national VA databases for 70 veterans who completed prolonged exposure or cognitive processing therapy at a Midwestern VA medical center. Utilization of services and cost data were examined for the year bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 20 publications
4
21
0
Order By: Relevance
“…Similarly, researchers at the Minneapolis VA noted a decrease in individual and group therapy after veterans had received treatment for PTSD, amounting to a 39.4% decrease in cost associated with mental health care (Meyers et al, 2013). Veterans with dually diagnosed PTSD and substance use disorder should thus be connected with services that utilize evidence-based PTSD treatment protocols.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, researchers at the Minneapolis VA noted a decrease in individual and group therapy after veterans had received treatment for PTSD, amounting to a 39.4% decrease in cost associated with mental health care (Meyers et al, 2013). Veterans with dually diagnosed PTSD and substance use disorder should thus be connected with services that utilize evidence-based PTSD treatment protocols.…”
Section: Discussionmentioning
confidence: 93%
“…Other studies have reported that Veterans who receive treatment with multiple interventions for PTSD and other trauma-related problems showed significant reductions in suicidal ideation, in addition to other benefits of treatment (Brown et al, 2016;Trockel et al, 2015;Walser et al, 2015). At the system level, VA researchers have documented mental health service and other cost offsets in the range of 30-40 percent associated with the delivery of EBTs for PTSD by trained therapists (Meyers et al, 2013;Tuerk et al, 2013).…”
Section: Veterans Health Administration Ebt Training Programmentioning
confidence: 99%
“…In one recent study, of 351 veterans who initiated EBP for PTSD, one third (n=135) dropped out before treatment completion [36]. Because completion of EBP not only significantly reduces mental health symptoms [37] but also positively impacts physical health and functioning while decreasing PTSD-related health care costs [38,39], enhancing veteran engagement is critical. Indeed, in one study, the original CALM program was not only found to be acceptable to both providers and patients but also resulted in substantial treatment engagement and homework compliance [20].…”
Section: Discussionmentioning
confidence: 99%